Akceptacja norm prawnych a opinie kandydatów do zawodu nauczycielskiego o idei odpowiedzialności za zdrowie własne i innych = Acceptance of legal norms in comparison with teachers trainees` opinions on the idea of responsibility for one`s health and the health of others - Kołecka, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to answer the following research question: How are teacher trainees prepared to perform professional duties related to the formation of responsibility for their own health and the health of others/students within the framework of health education? The author designed two questionnaires for the study. They concerned: the opinion on responsibility for one`s own health and the health of others, and the acceptance of legal norms by teacher trainees.
Keywords: normy prawne; idea odpowiedzialności za zdrowie; legal norms; idea of responsibility for health